(untitled) (Journal of the College of Basic Education, 2024)
This study aims to reveal the manifestations and manifestations of the symbolic tendency that l knew.The novel and linking it to its references and sources in our Arab and Islamic heritage.Symbol is one of the most important artistic techniques employed by the contemporary novel to diversity of its Semantic Worlds. Critics and researchers have realized the importance of the symbol through several studies that addressed it with research and analysis